Intramedullary Insertion of the Patellar Tendon, a Rare Anatomical Variant, Its Sequelae, and Surgical Management: A Case Report. Issue 3 (July 2019) - Collett, David J.; Sharma, Rahul; Goyal, Prateek
Abstract : Case: We report a rare cause of patella baja in a 25-year-old man presenting with right knee pain. He was found to have patella baja and a genu recurvatum deformity. Imaging revealed an extremely unusual variant of the patellar tendon—identified to have an intramedullary tibial insertion. A patellar tendon reconstructive procedure was performed. Conclusions: An intramedullary insertion of the patellar tendon is a fascinating and rare cause of patella baja with subsequent altered biomechanics of the extensor mechanism. We believe this is the first case report to describe its surgical presentation and an operative approach to its management.